Can International Law Limit Our Technological Imagination? On the Implications of the Customary Law Obligation of Prevention for SRM Governance - Katalin Sulyok (European Journal of Risk Regulation)
This article examines the role of customary international law in regulating SRM by analysing competing interpretations of the customary law principle of prevention and their implications for SRM governance. Existing customary law limitations are largely overlooked in current policy and expert discussions around the future of SRM, which seemingly proceed on the basis that there are no universally applicable limitations for states to develop SRM technologies should they decide so. The paper contrasts this view and argues, from a positivist point of view, that the customary principle of prevention does pose certain limits for states even before SRM-caused transboundary environmental harm occurs. It distinguishes between a retrospective and future-oriented dimension of the prevention principle, and it depicts three scenarios for how the prevention obligation may limit the development and deployment of SRM technology depending on how States (and international legal advisors) conceptualise the temporal scope and normative content of the prevention principle. The article also examines the implications of the different configurations of the customary law obligation for an eventual SRM treaty.